Marcel Duchamp und die Alten Meister: Zu den Vorbildern des radikalen Kunsterneuerers - Bethlen, Patricia (transcript, 2020)
Marcel Duchamp as a traditionalist? Analyses of his OEuvre for the first time in connection with Art of the Old Masters.